Britain - Time-Life Books (Amsterdam : Time-Life, 1985)
Photographs and text describe the land and people of Britain, the government and the monarchy, the economy, and the arts.
Includes bibliography and index.
School and library distribution by Silver Burdett, Morristown, New Jersey.
Wilson's Public Library.
7-10.
Young Adult
Keywords: Great Britain; Great Britain